2022
DOI: 10.3389/fsurg.2022.877206
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Association Between rs2439302 Polymorphism and Thyroid Cancer: A Systematic Review and Meta-Analysis

Abstract: Background and AimsThe extent of surgical treatment for most patients with thyroid cancer (TC) remains controversial and varies widely. As an emerging technology, genetic testing facilitates tumor typing and disease progression monitoring and is expected to influence the choice of surgical approach for patients with TC. Recent genome-wide association studies (GWASs) have identified that rs2439302 (8p12) variants near NRG1 are associated with TC risk; however, the results remain inconclusive. Therefore, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several studies demonstrated an association between NRG1 rs2439302 and PTC [ 62 , 63 , 64 ]. Moreover, a recent meta-analysis consolidated the previous results stating that the SNP rs2439302 variants of the gene encoding NRG1 carry a high thyroid cancer risk, especially in Chinese populations compared to Japanese populations or populations from the United States of America [ 65 ].…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 79%
“…Several studies demonstrated an association between NRG1 rs2439302 and PTC [ 62 , 63 , 64 ]. Moreover, a recent meta-analysis consolidated the previous results stating that the SNP rs2439302 variants of the gene encoding NRG1 carry a high thyroid cancer risk, especially in Chinese populations compared to Japanese populations or populations from the United States of America [ 65 ].…”
Section: Single Nucleotide Polymorphism and Thyroid Cancermentioning
confidence: 79%
“…In this study, we tried to clarify the underlying molecular mechanism. SNP rs2439302 was within the first intron of NRG1 on 8p12, which was first described to be significantly correlated with thyroid cancer (Guo et al, 2022). Thyroid hormones are important regulators of neurodevelopment early in life (Leung and Leung, 2019;Salerno et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the variants reported in the above-mentioned genes, there are also polymorphisms associated with TC ( 58 ). For instance, neuregulin 1 ( NRG1 ) acts as an oncogene through its role as a glycoprotein that mediates cell-to-cell signaling ( 59 ).…”
Section: Classical Point Mutations In Thyroid Cancer: Windows Of Oppo...mentioning
confidence: 99%